Perlindungan Hukum Ahli Waris atas Hibah yang Dibuat Secara Melawan Hukum: Studi Putusan Mahkamah Agung Nomor 3013K/Pdt/2022 - Dandi Saputra Harahap; Rosnidar Sembiring; Sutiarnoto (Jurnal Hukum Lex Generalis, 2025)
A grant deed constitutes a written instrument with full evidentiary force when executed in compliance with applicable legal requirements. In practice, however, grants are frequently made over inherited property that has not yet been partitioned, thereby giving rise to unlawful acts. This study analyzes legal protection for heirs, the validity of grant deeds derived from unlawful conduct, and judicial reasoning in Mahkamah Agung Decision No. 3013 K/Pdt/2022. Employing a normative juridical method with a descriptive-analytical approach based on secondary legal materials, this research finds that grant deeds concerning undivided inherited estates without the consent of all heirs are legally invalid and lack binding force, as they contravene inheritance law and infringe the subjective rights of co-heirs.